Analisis Pengukuran Kinerja Keuangan Pemerintah Daerah Kota Medan Menggunakan Value for Money Pada Badan Pengelola Keuangan dan Aset Daerah Kota Medan - Syahirah Syahirah; Muhammad Yafiz; Nur Fadhilah Ahmad Hasibuan (International Forum of Researchers and Lecturers, 2023)
This study aims to determine the measurement of the financial performance of the Regional Government of Medan City using value for money at the Regional Financial and Asset Management Agency of Medan City. This research uses a descriptive qualitative approach method. Data collection techniques in this study are in the form of interview techniques and documentation techniques. Based on the results of the study obtained namely, The Financial Performance of the Medan City Government as measured by the economic ratio from 2017-2021 can be said to be economical because based on the economic ratio calculated for 5 years, the overall average is 77%, which is included in the economic category because the economic ratio level is less than 100%. In terms of efficiency, from 2017-2021, the overall average is 95%, which is included in the efficient category because the efficiency ratio level is less than 100%. And in terms of effectiveness from 2017 – 2021, the overall average is 85%, which is included in the ineffective category because the effective ratio level is still below 100%.